2022
DOI: 10.30880/jtmb.2022.09.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Blockchain-based Mobile Banking Adoption: Evidence from a Developing Country

Abstract: This study attempts to explain the factors influencing blockchain-based mobile banking acceptance in Bangladesh. Based on a technology acceptance framework termed UTAUT2 (unified theory of acceptance and use of technology 2), an enhanced model with a mediating variable is built for this research. Data were collected from the first-ever blockchain-based mobile banking stakeholders in Bangladesh called 'UPAY' by applying a structured questionnaire. Structural equation modeling was then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…This hypothesis is supported to be in line with Davis (1989), Mostafa andEneizan (2018), andAkturan (2012), which shows that the diversity in function of mobile banking will attract Gen Z to adopt mobile banking. The risk level is the unique factor have a negative impact on Gen Z in acquiring mobile banking and that supports H4 (t=-5.409, p<0.001*) and is consistent with Kabir (2013), Al-Jabri and Sohail (2012) who also investigated the negative impact of this factor to limit the choice of Gen Z in using mobile banking distribution channel.…”
Section: Exploratory Factor Analysis (Efa)supporting
confidence: 82%
See 1 more Smart Citation
“…This hypothesis is supported to be in line with Davis (1989), Mostafa andEneizan (2018), andAkturan (2012), which shows that the diversity in function of mobile banking will attract Gen Z to adopt mobile banking. The risk level is the unique factor have a negative impact on Gen Z in acquiring mobile banking and that supports H4 (t=-5.409, p<0.001*) and is consistent with Kabir (2013), Al-Jabri and Sohail (2012) who also investigated the negative impact of this factor to limit the choice of Gen Z in using mobile banking distribution channel.…”
Section: Exploratory Factor Analysis (Efa)supporting
confidence: 82%
“…Risk Level Kabir (2013) has investigated the determinants and their impact on mobile banking usage in a developing country. The findings show the impacts of factors including privacy risk, social risk, financial risk, and time risk on the decision to use mobile banking.…”
Section: Safety and Confidentialitymentioning
confidence: 99%
“…The finding of this research has a differential concept that basically indicates the unique perception of young customer. Because this study finds that cost is the most influencing factor but security and conveyance has low influencing power, whereas most of the researches on mobile banking in Bangladesh reveal security, trust and assurance as the domination factor of determining customer satisfaction (Kabir, 2013;Jannat and Ahmed, 2015;Islam et al, 2019). Low income but adequate knowledge of Internet and mobile technology is the main feature of young generation that is the reason of this unique perception.…”
Section: Factors Effecting Customer Satisfactionmentioning
confidence: 81%
“…In Bangladesh, there also has some study about mobile banking. In order to identify the factors that influence the use of mobile banking in developing countries, Kabir (2013) made a research in Bangladesh and found easy use, usefulness, trust and relative advantage positively influence and risk negatively influence mobile banking adoption. Making a quantitative research only on 2nd generation bank, Jannat and Ahmed (2015) identified ineffective advertisement as negatively influencing factor of mobile banking.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation